Effects of root exposure on Honduras pine planting stock - Barres, Hester (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Four-month-old hydroponically grown plants averaging 12.8 cm in height were exposed to dive before planting in bare soil. After 21 minutes of exposure, subsequent mortality increased significantly. Growth in the upper plantation declined after five minutes of exposure.